Pengaruh Penerapan Senam Kaki Pada Penderita Diabetes Melitus Tipe Ii Di Rumah Sakit TK III Dr.R Soeharsono Banjarmasin - Ariani, Sri Purwanti; Jamilah, Sri (CV. ITTC INDONESIA, 2024)
Diabetes Mellitus is a non-communicable metabolic disorder that affects millions of people worldwide. It is associated with several micro and macrovascular complications and is also a leading cause of death. Type II Diabetes Mellitus cannot be cured but can be managed by adhering to the four pillars of Type II DM management, which include health education, meal planning or diet, regular physical exercise, and regular medication intake (Meirani, 2018). Individuals with Type II Diabetes Mellitus are often associated with obesity or an unhealthy lifestyle, as well as a lack of physical activity. The lack of physical activity or exercise is associated with an increased risk of hyperglycemia, and physical exercise becomes a useful strategy to help maintain blood sugar within the normal range. One type of physical exercise that can be done is leg exercises, as it can help regulate normal metabolism in the body and burn excess calories (Hasdianah, 2018).